Emission of nitrous oxide and methane from alluvial soil through incubation - Ray, Sanak; Mohanty, Ayusman; Ramulu, Torati Sri; Chaudhury, Gautam Roy (Journal of Environmental Engineering and Landscape Management, 2013)
Methane and nitrous oxide emission from alluvial soil under incubation using varying doses of urea and water content were studied for Tangibanta and Sorada. The N2O emission was observed to increase with time and tapers off after attaining the peak. The theoretical emission was evaluated using empirical equations and matches well with the experimental values. The CH4 and N2O emission both increased with the increase in Water Filled Pore Space (WFPS) and urea concentration. The nitrification and denitrification reaction rates were determined with and without acetylene. Michaelis-Menten equation was used to evaluate the Km and Vmax values. The rate of emission of N2O increased with increase of WFPS and urea concentration whereas the emission factor showed a reverse trend. The CH4 emission rate was observed to be comparatively low with respect to N2O emission rate around a factor of 10. First published online: 14 May 2013